THE WAY WOMEN’S FIGHT AGAINST PATRIARCHAL SYSTEM: A FEMINIST ANALYSIS TOWARDS PEARL S. BUCK’S IMPERIAL WOMAN - Wennyta . (Jurnal Ilmiah Dikdaya, 2017)
Abstract: This research is conducted to show that woman not always passive, weak or inferior side, but she can use her inferiority (from patriarchal point of view) as a tricky strategy to get the equality between men and women. It is described in Imperial Woman, where Yehonala succeeds in arranging many strategies inside the oppression from patriarchal system. In collecting the data, the writer conducts a library research. A novel by Pearl S. Buck, entitled Imperial Woman and also the biography of Buck are chosen as the primary data of this research. From the sources the writer takes any data about the women’s struggle toward patriarchal system. Furthemore, the writer uses descriptive method. So, the writer will write a thesis by describing the result of this research in descriptive way. The result of the analysis shows that Feminist approach and Buck as a female author teaches and reminds people that woman is a very special creature. Woman is not a weak person. She explores all and she has to attack the man’s position and in order to be respected by man like Yehonala did.Keyword :Patriarchal System, Pearl S. Buck’s Imperial Woman